2021
DOI: 10.3390/foods10020307
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues and Their Metabolites in Grapes and Wines from Conventional and Organic Farming System

Abstract: In this study, the occurrence of pesticide residues and their metabolites in grapes and wines was investigated. A targeted analysis of 406 pesticide residues in 49 wine and grape samples from organic and conventional production were performed using the QuEChERS (Quick, Easy, Cheap, Effective, Rugged and Safe) extraction method, followed by ultra-high-performance liquid chromatography coupled with tandem mass spectrometry. Multiple residues (>4 residues/sample) were detected in 22 tested samples. The most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…During the grape cultivation period, it is common practice in vineyards to use pesticides, such as fungicides, insecticides and herbicides, to obtain high production. Grapes receive multiple doses of pesticides, which may partly transfer into wine [4][5][6][7][8]. In previous market surveillance studies [9][10][11][12][13], metalaxyl, procymidone, fenhexamid, cyprodinil, azoxystrobin and iprodione were detected in commercial grape wines; tebuconazol, metalaxyl and cyprodinil represent the most frequently detected pesticides.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…During the grape cultivation period, it is common practice in vineyards to use pesticides, such as fungicides, insecticides and herbicides, to obtain high production. Grapes receive multiple doses of pesticides, which may partly transfer into wine [4][5][6][7][8]. In previous market surveillance studies [9][10][11][12][13], metalaxyl, procymidone, fenhexamid, cyprodinil, azoxystrobin and iprodione were detected in commercial grape wines; tebuconazol, metalaxyl and cyprodinil represent the most frequently detected pesticides.…”
Section: Introductionmentioning
confidence: 94%
“…Grape wine samples, including fifty red grape wines and twenty white grape wines, were purchased at supermarkets in Beijing and they belonged to several vintages between 2011 and 2018. Seventy samples were produced in wineries from different countries: China (42), France (7), Spain (5), Portugal (5), Italy (4), Australia (4) and the USA (3). The alcoholic strength ranged from 10% to 15% (Alc/vol).…”
Section: Analysis Of Grape Wine Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Union is the world’s largest wine producer with a production volume of around 156 million hectoliters per year [ 5 ]. To protect grapevines ( Vitis vinifera L.) from competing weeds, bacterial and viral diseases, fungi, insects, and further pests, they are commonly treated with pesticides [ 6 , 7 ]. Depending on factors such as chemical structure and physicochemical properties of the substances, but also ecophysiology, and weather conditions (e.g., humidity, rainfall, temperature), as well as agronomic practices, pesticide residues sometimes remain in or on the grapes at harvest [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several pests and diseases affect grapevine production; thus, an intensive pesticide schedule is often required to meet production standards [39]. Nevertheless, it has been demonstrated that a continuous use of plant protection products has several negative implications for the environment and human health [40,41]. Consequently, there is a strong need to explore and re-valorize strategies to achieve sustainable production standards.…”
Section: Introductionmentioning
confidence: 99%